Análise dos processos de avaliação de impacto ambiental em usinas fotovoltaicas e o potencial biofísico no nordeste do Brasil - Lima, Paulo de Tarso Dantas (2021)
Electricity generation by photovoltaic systems has been growing exponentially all over the world. The implementation of this type of activity requires the preparation of several studies, including the Environmental Impact Assessment (EIA). Therefore, it is imperative to improve this tool, as it is the main instrument in ensuring the promotion of sustainable development in the segment. Another process to be improved is decisionmaking regarding the installation areas of photovoltaic projects, which can occur through the use of geographic information systems and environmental criteria, also considering socioeconomic aspects, among others. Thus, this work aims to evaluate the quality and applicability of EIAs to photovoltaic projects, from the identification of beneficial and adverse impacts and the measurement of the biophysical potential of the Northeast region. For that, documental research was used, through the analysis of 41 EIAs, through which it was possible to identify 3381 impacts, subdivided in the planning, implantation, operation and deactivation phases of the projects. Regarding the biophysical potential, this was calculated based on three environmental criteria: average land slope, land cover classes and global horizontal solar irradiation (GSI). It was found that 75% of the impacts are expected to occur during the implementation of the projects. When analyzing the environmental compartments, it is noticed that 82% and 76.5% of the impacts incident on the biotic and abiotic environments, respectively, are negative. In the socioeconomic environment, 72.2% are positive. The biophysical potential indicated high environmental viability for the production of photovoltaic energy, given the favorable conditions of slope, high GSI and land cover classes compatible with the activity. Thus, only 5.47% of the territory is environmentally unviable; 9.58% have viability between 37.7% and 58.4%; in 27.88% the potential ranged between 58.4 and 79.0%; while 57.07% proved fit, with up to 99.7%. The historical quantification of environmental impacts can be used to assess the benefit of the activity in cities and regions, and to score the most relevant impacts. It was also possible to observe that some impacts referenced in the international literature are not foreseen in the EIAs studied, a fact that can compromise decisionmaking by the government. As for the environmental feasibility of photovoltaic energy generation, based on biophysical parameters, it was found that the Northeast region has a high potential in almost all of its territory. With a view to the sustainable development of this region, it is pertinent to promote the identification of suitable areas for the generation of photovoltaic energy, since it allows transmission planning, provides subsidies for the elaboration of plans, programs and public policies; it expands the certainties of the solar energy market and protects environmentally sensitive areas, in order to combine the generation of photovoltaic energy with the minimization of unwanted environmental impacts.